Saint-Saëns's First String Quartet, Cyclic Form and the Aesthetics of Charm. Issue 1 (12th April 2020) - Deruchie, Andrew
Abstract : From the 1850s, Saint-Saëns regularly employed cyclic form: the practice of establishing large-scale relationships (especially in symphonies, chamber works, etc.) by reintroducing materials from earlier movements in later ones. Nonetheless, he became weary of such procedures following the Third Symphony (1886) for cultural-political reasons: Franck's most important cyclic works date from the 1880s, d'Indy declared la forme cyclique a historically determined canon, and period writers considered cyclic form a franckiste hallmark – all while Saint-Saëns's relationship with Franck's followers deteriorated. In this essay, I argue that Saint-Saëns's First String Quartet (1899) 'misreads' his rivals' approaches to cyclic form as exemplified by d'Indy's Second Quartet of 1897 (in which a four-note cell suffuses most themes) and Franck's Quartet (in which themes from previous movements climactically accumulate in the final coda). Saint-Saëns's themes abound with miniscule motivic connections, which catch listeners' ears but seem too fleeting and insubstantial to register as binding elements comparable to d'Indy's pellucid cell. Such relationships straddle the threshold of apprehensibility, and they produce a distinctive affective quality: where d'Indy fosters perceptions of genetic relationships, Saint-Saëns elicits a sensation of déjà entendu. The final coda similarly teases by reintroducing fragments from the slow introduction, encouraging anticipation of a Franck-like apotheosis. What follows is a mirage of one: timbres and textures of previous movements return, but incipient citations of themes dissolve. Where Franck delivers a full-blooded synthesis, Saint-Saëns follows through with trompe l'oreille . Saint-Saëns's misreadings of franckiste technique point to broader aesthetic conflicts. D'Indy enlisted cyclic form as a means to monumentality, which served the enseignement he esteemed as art's purpose. Déjà entendu and trompe l'oreille, on the other hand, register as classicising attributes which diverge from d'Indy's didactic objectives and which Saint-Saëns grouped under the rubric of 'charm', a conduit to what he considered an ideologically neutral 'aesthetic sense'.